The Movement Of Sarekat Islam's Politics In Struggling National Independence In 1918-1945 - Maftuhin Maftuhin; Sumarjono Sumarjono; Nurul Umamah (JURNAL HISTORICA, 2017)
Sarekat Islam is a movement organization becoming a vanguard of appearing a modern political movement in Indonesia. The encouragement of Sarekat Islam as political movement stimulates new ways of Indonesian in facing colonialism for national independence of Indonesia. This study aims to analyze many political movements done by Sarekat Islam such as diplomatist, strike, propaganda, even a protest in the attempt of achieving national independence. The research questions in this study are the Sarekat Islam's attempts in changing a fight into politics field, what types of Sarekat Islam's fight in a political field, and how the effect of Sarekat Islam's fight in the political field. The research uses a historical study method of heuristics step (collecting data), critic (through the validity of sources that had been gotten from the heuristics process), interpretation (interpretation toward the sources gotten), historiography (providing a result of a study in a writing form). This study uses a theory of conflict and political sociology approach. The finding of the study shows that the change of Sarekat Islam leadership from Haji Samanhudi to Tjokroaminoto make a new fight in the field politics. The change is also motivated by the appearance of Indie Werbaar establishment (Hindia defence) and Volksraad (house of people’s representatives). So it makes Sarekat Islam changes its movement into a dynamic political movement. Many political fights are done by Sarekat Islam thorough Volksraad, labour movement, Pan-Islam movement, and PPPKI national federation (Indonesian political nationalism association conciliation) and GAPI (Indonesian political alliance). Beside inspiring much another organization movement to fighting in the field of politics, the political movement of Sarekat Islam also stimulates many new fighting to oppose Dutch colonialism and it becomes the most important thing for the movement organization in achieving national independence of Indonesia. Keywords: a political movement, Sarekat Islam, struggle, independence.